Developing competent leaders in Malaysian Higher Education: An interview with the Vice- Chancellor of Universiti Malaya, Y.Bhg. Datuk Rafiah Salim. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
To compete with the best in the world, and hence be recognised as world class, universities must establish a strong academic reputation.